Virtues of Proximity - Gabriel Cuéllar; Athar Mufreh (Footprint)
Whereas real estate-driven development tends to invest in singular and concentrated sites, resident-led development thrives in scattered patterns. The properties of community land trusts (CLTs) — one of the foremost models of resident-led development whereby land is claimed and used by a community without landlords — are almost always dispersed in a context where every property line is a potential obstacle to development. What these populist landholdings lack in terms of economy of scale is compensated for by virtues of proximity. This article examines the historic phenomena of property scattering and spatial patterns of CLTs across the US, articulating the possibility of designing patterns of scattered landholdings that support the values of resident-led development.